An examination of the curvilinear relationship between workplace ostracism and knowledge hoarding. Issue 2 (20th March 2017) - Zhao, Hongdan; Xia, Qing
Abstract : Purpose: The purpose of this paper is to explore the curvilinear relationship between workplace ostracism (supervisor ostracism and co-worker ostracism) and knowledge hoarding by using the conservation of resources theory. In addition, the paper predicts one possible situational context (political skill) that may influence employees' reaction to ostracism. Design/methodology/approach: Using a two-wave research design, the authors collected data from 240 samples in a Chinese diversified company. Hierarchical regression models were used to test the hypotheses. Findings: The authors found that the relationship between workplace ostracism (supervisor ostracism and co-worker ostracism) and knowledge hoarding was U-shaped. Moreover, political skill moderated the linkage between workplace ostracism and knowledge hoarding such that the U-shaped association was stronger for people higher, rather than lower, in political skill. Originality/value: By exploring a curvilinear relationship between ostracism and knowledge hoarding, the study enriches the knowledge hoarding literature by adding a substantive predictor of knowledge hoarding. The findings can also extend the workplace ostracism literature by providing a new conceptual analysis of interpreting the inconsistent findings involving the influence of workplace ostracism. Moreover, identifying political skill as a moderator can gain a better understanding of when and why an ostracized employee's knowledge hoarding behavior can be less likely.